The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1038/s41467-022-32711-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent climate change has driven divergent hydrological shifts in high-latitude peatlands

Abstract: High-latitude peatlands are changing rapidly in response to climate change, including permafrost thaw. Here, we reconstruct hydrological conditions since the seventeenth century using testate amoeba data from 103 high-latitude peat archives. We show that 54% of the peatlands have been drying and 32% have been wetting over this period, illustrating the complex ecohydrological dynamics of high latitude peatlands and their highly uncertain responses to a warming climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…However, our studied peatland was dominated by S. fuscum during the bog phase and we found lower accumulation rates for the upper sections in the catotelm layer during the bog phase (789–111 cal year BP), suggesting the dominant role of external forcing in the CAR of our studied peat core. Other previous researches with similar conditions to ours (i.e., vegetation shift caused by volcanic eruption) also reported this pattern (Ratcliffe et al, 2020; Zhang, Smol, et al, 2022; Zhang, Väliranta, et al, 2022). They used measured CAR in their studies due to the high impacts of external forcing.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, our studied peatland was dominated by S. fuscum during the bog phase and we found lower accumulation rates for the upper sections in the catotelm layer during the bog phase (789–111 cal year BP), suggesting the dominant role of external forcing in the CAR of our studied peat core. Other previous researches with similar conditions to ours (i.e., vegetation shift caused by volcanic eruption) also reported this pattern (Ratcliffe et al, 2020; Zhang, Smol, et al, 2022; Zhang, Väliranta, et al, 2022). They used measured CAR in their studies due to the high impacts of external forcing.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies also found that an acidic SO 2 plume derived from volcanic ash facilitated Sphagnum establishment and carbon accumulation in peatlands (Loisel & Bunsen, 2020; Ratcliffe et al, 2020). Phosphorus (P) can be released from tephra for decades and therefore we believe P concentration during the bog phase after tephra deposition was not too low, which was reported in previous findings in the same area as our study (Zhang, Smol, et al, 2022; Zhang, Väliranta, et al, 2022) and in the Utasai Bog in Japan (Hughes et al, 2013). The peatland was most likely more limited by N than by P, affecting both decomposition and CAR.…”
Section: Discussionsupporting
confidence: 85%
“…In turn, water level drawdown experiments on high‐latitude peatlands have shown that drier conditions result in shrub domination over mosses and forbs, such conditions also sustaining high belowground production (Mäkiranta et al, 2018). However, in the northeast Canada, a regime sift from sedges to Sphagnum domination has been documented (Magnan et al, 2022) and centennial peatland drying trend in low latitude Europe (Swindles et al, 2019) and high latitude Eurasian continent is observed from other peatland proxies (testate amoebas) but with more variable signal for North American continent (Zhang et al, 2022). Our results provide valuable information to add on the understanding of global peatland vegetation changes, their response sensitiveness, and complement the hydrological information produced by testate amoebas.…”
Section: Resultsmentioning
confidence: 99%
“…Warming that generally increases evapotranspiration has been predicted to result in drying of northern peatlands (Helbig et al, 2020; Swindles et al, 2019), and studies suggest that northern peatlands especially respond to changes in moisture conditions quicker and more prominently than more southern peatland types (Gong et al, 2013; Kokkonen et al, 2019; Tahvanainen, 2011). A new data compilation based on hydrologically sensitive organisms, testate amoebae, indicates a large‐scale change of high‐latitude Eurasian peatlands toward drier conditions, while in North American continent, the signal is weaker (Zhang et al, 2022). However, in permafrost peatlands, warming may lead to abrupt or more gradual thawing and consequent wetting (Hugelius et al, 2020; Turetsky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Peatland contains a large amount of plant litter and humus, which is vulnerable to fire due to lightning strikes or human activities in extreme drought conditions (Rein et al, 2008). As global warming becomes more pronounced, climate change and human activities are decreasing the depth of the water table of peatlands (Swindles et al, 2019; Zhang et al, 2022), which is leading to high frequency peat fire incidents (Turetsky et al, 2014; Virtanen et al, 2013). For example, during the summers of 2002 and 2010, additional peat megafires occurred in central Russia, resulting in months of peat‐burning smog in Moscow and a 1.6‐fold increase in mortality (Chubarova et al, 2008, 2012).…”
Section: Introductionmentioning
confidence: 99%